Neuroinflammation in HIV-Related Neuropathic Pain - Lu, Huan-Jun; Fu, Yuan-Yuan; Wei, Qian-Qi; Zhang, Zhi-Jun (Frontiers in Pharmacology, 2021)
In the management of human immunodeficiency virus (HIV) infection around the world, chronic complications are becoming a new problem along with the prolonged life expectancy. Chronic pain is widespread in HIV infected patients and even affects those with a low viral load undergoing long-term treatment with antiviral drugs, negatively influencing the adherence to disease management and quality of life. A large proportion of chronic pain is neuropathic pain, which defined as chronic pain caused by nervous system lesions or diseases, presenting a series of nervous system symptoms including both positive and negative signs. Injury caused by HIV protein, central and peripheral sensitization, and side effects of antiretroviral therapy leads to neuroinflammation, which is regarded as a maladaptive mechanism originally serving to promote regeneration and healing, constituting the main mechanism of HIV-related neuropathic pain. Gp120, as HIV envelope protein, has been found to be the major toxin that induces neuropathic pain. Particularly, the microglia, releasing numerous pro-inflammatory substances (such as TNFα, IL-1β, and IL-6), not only sensitize the neurons but also are the center part of the crosstalk bridging the astrocytes and oligodendrocytes together forming the central sensitization during HIV infection, which is not discussed detailly in recent reviews. In the meantime, some NRTIs and PIs exacerbate the neuroinflammation response. In this review, we highlight the importance of clarifying the mechanism of HIV-related neuropathic pain, and discuss about the limitation of the related studies as future research directions.